2023
DOI: 10.48165/ijvsbt.19.2.08
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Management Practices of Gir Cattle followed in Gujarat, India

Abstract: The present study  was undertaken to collect information on feeding management practices of Gir cattle at Junagadh district and data were ascertained from randomly selected 320 Gir cattle owners through personal interview with the help of pre-tested structured schedule from four randomly selected talukas of Junagadh district, Gujarat. Majority of Gir cattle owners (86.88%) followed stall feeding system and most of them (93.44%) cultivated green fodder crops for feeding of Gir cattle. Majority (81.56%) of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was revealed that overall, 72.00 per cent of cattle owners prefer pucca manger for feeding, 19.33 per cent use kuccha manger for feeding and remaining 08.67 per cent had no manger for feeding. In the pucca manger majority of i.e., 46.00 per cent use cement constructed manger for feeding and 26.00 per cent prefer steel manger (Kasondra et al, 2022). From the above observation it was revealed that overall, about 62.67 per cent didn't used bedding material on the floor in winter season because wastage of fodder and only 37.33 per cent cattle owners used bedding material.…”
Section: Housing Management Practicesmentioning
confidence: 92%
“…It was revealed that overall, 72.00 per cent of cattle owners prefer pucca manger for feeding, 19.33 per cent use kuccha manger for feeding and remaining 08.67 per cent had no manger for feeding. In the pucca manger majority of i.e., 46.00 per cent use cement constructed manger for feeding and 26.00 per cent prefer steel manger (Kasondra et al, 2022). From the above observation it was revealed that overall, about 62.67 per cent didn't used bedding material on the floor in winter season because wastage of fodder and only 37.33 per cent cattle owners used bedding material.…”
Section: Housing Management Practicesmentioning
confidence: 92%